Experimental Design Optimization of Castor Oil, Phthalic Anhydride, and Glycerin Magnetic Nanocomposites Useful as Oil Spill Cleanup Tool. Issue 1 (16th August 2018) - Lopes, Magnovaldo C.; Marques, Fernanda; Souza, Fernando G.; Oliveira, Geiza E.
Abstract : Experimental design technique (DoE) is applied to determine the best chemical composition of alkyd resins used as a matrix in magnetizable composites, which are an excellent tool in aquatic environmental cleanup processes. The alkyd resins are obtained from phthalic anhydride, castor oil, and glycerin, a byproduct of biodiesel production, that makes this kind of matrix ecologically friendly polymeric materials. Maghemite nanoparticles are used as filler in the prepared magnetizable composites. Obtained materials are characterized using wide‐angle X‐ray diffraction (WAXD), small angle X‐ray scattering (SAXS), infrared spectroscopy with Fourier transformed (FTIR), and ultraviolet‐visible spectroscopy (UV‐Vis). Besides, magnetic force test and oil removal capability test, which is the most important property in this case, are also performed. According to experimental results, melt mixing process used to prepare these nanocomposites do not change the monodomains size of the nanoparticles. On the other hand, the nanocomposites present magnetic force higher than the one from the pure maghemite, probably due to a better distribution of the nanoparticles inside the matrix. Also, composites present an excellent oil cleanup capability, since, in the best case, 1 g of the hybrid material is able to remove more than 20 g of the oil from the water.